NEW RECORDS OF BATS IN THE PROVINCE OF TRIESTE (FRIULI VENEZIA GIULIA REGION), NORTHEASTERN ITALY - MAJA ZAGMAJSTER; AILA QUADRACCI; FILACORDA, Stefano (2011)
NEW RECORDS OF BATS IN THE PROVINCE OF TRIESTE (FRIULI VENEZIA GIULIA REGION), NORTHEASTERN ITALY By: Zagmajster, Maja; Quadracci, Aila; Filacorda, Stefano Atti del Museo Civico di Storia Naturale di Trieste Volume: 55 Pages: 13-23 Published: 2012 Context Sensitive Links Close AbstractClose Abstract New records of bats in the Province of Trieste (Friuli Venezia Giulia Region), Northeastern Italy - In the Province of Trieste recent information on bats is lacking, with no significant information on bat fauna for more than 15 years. A short bat study was conducted on three days and nights in the end of July 2008. By implementing different research methods, we recorded at least nine bat species on six out of twelve localities, and observed signs of bat presence (droppings) at additional two. Six bat species were mistnetted: Hypsugo savii, Myotis bechsteinii, Myotis nattereri, Plecotus macrobullaris, Eptesicus serotinus and Barbastella barbastellus. The species or groups of species, that were detected with ultrasound detectors only, were Pipistrellus kuhlii/nathusii, Myotis sp. and Rhinolophus hipposideros, the latter near the probable cave roost. One individual of Rhinolophus ferrumequinum was observed at one cave. Three bat species (M bechsteinii, M nattereri and P macrobullaris) were recorded in the province for the first time. Reproduction of four species was confirmed, either by mistnetting lactating females (M. bechsteinii, M nattereri, H. savii) or juvenile individuals (E. serotinus). Despite very short time of research, gathered results indicate rich bat fauna in the province. Further study of bat distribution and ecology in the area would be necessary.